Peningkatan Keterlibatan Peserta Didik pada Pembelajaran Jarak Jauh dengan Menggunakan Fitur Lesson Quizizz - Asri Maspupah; Sri Ratna Wulan (STMIK Budi Darma, 2021)
The implementation of distance learning in Informatics Engineering has many problems, one of which is the lack of student engagement during learning. The purpose of this study is to improve student engagement by using a feature called Lesson in Quizizz. Lecture teaches on video teleconference and instructs students on Lesson in Quizizz to interact and give feedback about the lesson. The survey method is the research method used for this study. At the end of the semester, students are given a questionnaire regarding increasing interest in learning with conventional methods and the Lesson Quizizz added. The results showed that the student engagement using the Lesson Quizizz features increased by 4.5% compared to conventional learning. Indicators of student engagement have a high increase along with the improvement of student concentration. Thus, Quizizz can encourage students who usually are not active in class